2006
DOI: 10.1007/s00397-006-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

Aging of an unstable w/o gel emulsion with a nonionic surfactant

Abstract: International audienceWe study an unstable highly concentrated emulsion of water droplets in oil with a nonionic surfactant. A technique of light diffusion coupled to a rheometer allows simultaneous measurement of average droplet radius R and emulsion shear elastic modulus G' during time. Over the studied range of volume fraction (from 71 to 95%), we show that Princen and Kiss' (J Colloid Interface Sci 112: 427-437, 1986) model does not apply. A dimensional analysis based on the hypothesis of dominant van der … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 14 publications
3
39
0
Order By: Relevance
“…This is not the only such result published. Mougel et al (2005) also observed the same type of G versus D dependence and in Bengoechea et al (2006) it was concluded that ''the elastic modulus may be much higher than that predicted by Mason's law.'' This principle contradiction of the basic theoretical models forced us to undertake a much more extensive experimental investigation to ensure that Equation (3) does not represent an occasional result.…”
Section: Introductionmentioning
confidence: 77%
“…This is not the only such result published. Mougel et al (2005) also observed the same type of G versus D dependence and in Bengoechea et al (2006) it was concluded that ''the elastic modulus may be much higher than that predicted by Mason's law.'' This principle contradiction of the basic theoretical models forced us to undertake a much more extensive experimental investigation to ensure that Equation (3) does not represent an occasional result.…”
Section: Introductionmentioning
confidence: 77%
“…The relationship between the rheological behavior of concentrated and highly concentrated emulsions and the average droplet size (droplet size distribution) has also been the subject of numerous publications (Jager-Lézer et al, 1998;Pal, 1998a,b;Malkin et al, 2004;Mougel et al, 2006;Pal, 2006;Derkach, 2009;Capdevila et al, 2010). A comparison of Figs.…”
Section: Part I: Multi-scale Approachmentioning
confidence: 97%
“…To describe the elastic properties of a disordered droplet packing, they used a model that replaces the droplets with soft spheres that interact with their nearest neighbors through central-force potentials that reflect the behavior of the facets. 8,20 In a previous research note, 17 we have already reported and compared different models found in the literature, and we described, with more detail, the models proposed by Mougel et al, 14 Masalova and Malkin, 15 and Foudazi et al 16 More specifically, we carefully analyzed the Princen and Kiss model, since it is a rigorous detailed model that is derived from pressure/ volume surface relationships, leading, in particular, to an expression relating the geometric and thermodynamic properties of highly concentrated monodisperse emulsions to their elastic modulus. 3,5 However, a phenomenological function E(ϕ) had to be introduced to accommodate experimental deviations.…”
Section: Introductionmentioning
confidence: 92%